Impact of estradiol-valerate dienogest on work productivity and activities of daily living in European and Australian women with heavy menstrual bleeding - Wasiak R; Filonenko A; Vanness DJ; Wittrup-Jensen KU; Stull DE; Siak S; Fraser I (Dove Medical Press, 2012)
Radoslaw Wasiak,1 Anna Filonenko,2 David J Vanness,3 Kim U Wittrup-Jensen,2 Donald E Stull,1 Steven Siak,1 Ian Fraser41Centre for Health Economics and Science Policy, United BioSource Corporation, London, United Kingdom; 2Global Health Economics and Outcomes Research, Bayer Healthcare Pharmaceuticals, Berlin, Germany; 3University of Wisconsin, Madison, WI, USA; 4Department of Obstetrics and Gynaecology, University of Sydney, Sydney, NSW, AustraliaBackground: The purpose of this study was to quantify the impact of estradiol valerate-dienogest (E2V/DNG; Qlaira®/Natazia®) on work productivity and activities of daily living in European and Australian women with heavy menstrual bleeding.Methods: Women aged 18–54 years with a confirmed diagnosis of heavy menstrual bleeding and no recognizable pathology were recruited across nine European countries (the Czech Republic, Finland, Germany, Hungary, The Netherlands, Poland, Sweden, UK, and Ukraine) and Australia. The women were randomized to receive either E2V/DNG (n = 149) or placebo (n = 82) for seven treatment cycles (196 days). The outcomes assessed included work productivity (ie, productivity while at work) and activities of daily living, measured on a Likert scale from 0 to 10 (with higher values denoting higher impairment levels) at baseline and at the end of the third and seventh cycles (days 84 and 196). The equivalent monetary value associated with the changes in work productivity and activities of daily living was also calculated.Results: Across all the countries, greater improvements from baseline to the end of treatment were observed with E2V/DNG treatment than placebo in work productivity (46.0% versus 15.1%) and activities of daily living (55.6% versus 30.8%). In 2008, savings associated with improvements in work productivity and activities of daily living due to E2V/DNG treatment (net of placebo improvement) were estimated to be between US$22–62 and US$18–56 per month (in purchasing power parity of US$), respectively.Conclusion: E2V/DNG has a consistent positive impact on work productivity and activities of daily living in European and Australian women with heavy menstrual bleeding. These improvements were associated with a reduction in monetary burden of heavy menstrual bleeding compared with the placebo group, consistent with the response to treatment observed.Keywords: heavy menstrual bleeding, work productivity, activities of daily living, estradiol valerate, and dienogest